The Influence of Customer Relationships on Supply Chain Risk Mitigation in International Logistics - Muhammad Ilyas; Zhihong Jin; Irfan Ullah; Qasim Zaheer; Waiss Ali Aden (Civil Engineering Journal, 2024)
Adequate transportation and administration of products and resources across borders are crucial in the logistics industry, particularly in locations such as the China-Pakistan Economic Corridor (CPEC). However, other hazards are associated with this, including global disputes, geopolitical tensions, trade battles, natural catastrophes, terrorist threats, and security breaches, all of which can disrupt the supply chain. These hazards highlight the need for robust supply chain risk management (SCRM) strategies to ensure the seamless distribution of products and services in the face of adversity. To address these challenges, this study examines the impact of customer relationships (CR) on supply chain risk management in the CPEC logistics sector. A survey conducted across various transportation and logistics firms' sites obtained data from 500 staff members. After removing 50 partial replies, 450 total responses were considered. The information also includes reactions for operational supply chain risk management (OSCRM), organization performance (OP), strategic supply chain risk management (SSCRM), and customer relationship (CR). To evaluate the respondents of the survey questionnaire using the Likert scale. Partial least squares structural equation modeling (PLS-SEM) is utilized to validate the hypothesis, which is used for statistical analysis, validation of structural models, and measurement models. The measurement model established the measure's validity and reliability, while other approaches demonstrated discriminant validity. The structural model is employed to identify the significant relationships between CR and SCRM in the logistics sector. The findings emphasize CR's importance in managing the supply chain's inherent constraints, contributing to CPEC's sustainability. Overall, this research attempts to enhance understanding of the complex relationship between CR and SCRM in the dynamic world of global logistics. Doi: 10.28991/CEJ-2024-010-06-010 Full Text: PDF